2005
DOI: 10.1159/000088396
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Patients with Gastric Inflammation: A Systematic Review

Abstract: Background: The importance of examining the status of gastric inflammation has been acknowledged; the new classification by the updated Sydney system (USS) allows us to evaluate the quantitative status of gastric inflammation. However, this system is based on the histological classification derived from biopsy specimens. Therefore, more convenient, objective and practical biomarkers are recommended. Aim: We undertook a systematic review to find out potential biomarkers by summarizing the relationship between b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
45
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 284 publications
4
45
0
1
Order By: Relevance
“…As is well known, IL-8 is a key cytokine that enhances H. pyloriinduced gastric inflammation showing mononuclear cell/neutrophil infiltration in the mucosal layer (28). We showed the possibility that bile acid first has an inhibitory effect on CINC1 expression induced by H. pylori infection, and second, inhibits the infiltration of inflammatory cells in the gastric mucosa.…”
Section: Discussionsupporting
confidence: 50%
“…As is well known, IL-8 is a key cytokine that enhances H. pyloriinduced gastric inflammation showing mononuclear cell/neutrophil infiltration in the mucosal layer (28). We showed the possibility that bile acid first has an inhibitory effect on CINC1 expression induced by H. pylori infection, and second, inhibits the infiltration of inflammatory cells in the gastric mucosa.…”
Section: Discussionsupporting
confidence: 50%
“…In our study, we observed neither a change in the gastrin level nor in GERD occurrence between H. pylori-infected and non-infected state. In contrast to these hypotheses, we could not demonstrate any relationship between gastrin and GERD, which was comparable with a few studies in the literature (18)(19)(20)(21)(22)(23)(24). One of the reasons for this difference can be the predominant corpoantral infection in our patients.…”
Section: Discussionsupporting
confidence: 79%
“…IL-8 production in the gastric mucosa has been shown to be induced by H. pylori infection and to correlate with the development of chronic gastritis (16). IL-8 production is also recognized as an early response to H. pylori by the gastric epithelium (14).…”
Section: Discussionmentioning
confidence: 99%
“…Among these cytokines, IL-8 is the most highly expressed gene in H. pylori-infected gastric epithelial cells and appears to play a major role in the epithelial cell response to H. pylori infection and in the pathological processes leading to gastric disease (14,15). Several studies have demonstrated increased IL-8 production and secretion in response to H. pylori both in vivo and in vitro (16,17). Gastric mucosal IL-8 levels show a positive correlation with the degree of stomach corpus inflammation, and IL-8 expression is also highly increased in gastric cancer (18,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation